Cost benefit analýza regionálního inovačního systému Jihomoravského kraje - Koťátková Stránská, Pavla; Maťátková, Kateřina; Stejskal, Jan (Univerzita Pardubice, 2012)
The knowledge and innovation have the important role of regional economics at present. It can be said that innovation are the cornerstone of economic growth. Each region is trying to encourage innovation by certain tools. There is no universal access, how to effectively create a suitable environment for the emergence and spread of innovation. In this context, regional innovation systems were developed and regions are become centers of innovation. Innovation arises at the regional level through regional innovation network of innovative companies, and local industrial clusters with significant contributions from academic institutions in the region. This paper will focus on evaluation of the usefulness of the funds spent on the creation of regional innovation system in the South Moravian region. To evaluated CBA - Cost Benefit Analysis method was chosen. The paper of course includes graphical interpretation of results. Input data for the application of the CBA are obtained from public statistical yearbooks.
The cost benefit analysis of the regional innovation system of the South Moravian region
Keywords: RIS; innovation; knowledge; CBA